Rancang Bangun Sistem Informasi Dasbor Analitik Indikator Kinerja Pelayanan Rumah Sakit (Simpel-Sifat) Berbasis Web Menggunakan Framework Laravel RSUD Siti Fatimah - Juliansa Juliansa; A. Haidar Mirza (Lembaga Pengembangan Kinerja Dosen, 2026)
The South Sumatra Provincial Hospital, RSUD Siti Fatimah, continuously generates substantial amounts of medical data across multiple departments, including outpatient, inpatient, and emergency care. However, the fragmentation of these data sources frequently hinders the effective tracking of service metrics and medical audits, complicating critical evaluation and strategic governance. To address this challenge, this research outlines the design and implementation of SIMPEL-SIFAT, a web-based analytical dashboard for monitoring hospital performance indicators, engineered utilizing the Laravel framework. The development lifecycle encompassed comprehensive requirements gathering, architectural planning utilizing the Model-View-Controller (MVC) paradigm, and backend integration using Microsoft SQL Server. Functional validation was thoroughly conducted via Black Box Testing. The resulting platform delivers dynamic visualizations of essential operational metrics—such as Bed Occupancy Rate (BOR), Length of Stay (LOS), and Turn Over Interval (TOI)—alongside robust service audit capabilities and streamlined patient data retrieval. Evaluation outcomes demonstrate that the system performs strictly in accordance with specified requirements, effectively facilitating continuous data processing and oversight. Ultimately, SIMPEL-SIFAT successfully consolidates clinical data to provide actionable insights, empowering data-driven decision-making and significantly enhancing the efficiency of monitoring frameworks at RSUD Siti Fatimah.